2019
DOI: 10.1186/s12864-019-5553-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparing DNA methylation profiles in saliva and intestinal mucosa

Abstract: Background Altered epigenetic profiles are a feature of intestinal diseases, including ulcerative colitis and Crohn’s disease. DNA methylation studies in these diseases have utilised intestinal mucosal tissue or blood which can be difficult to collect, particularly for large-scale research studies. Saliva is an attractive alternative for epigenetic studies as it is easy to collect and provides high quality methylation profiles. The aim of the study was to determine the utility of saliva as an alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…It is unknown whether the differences in DNA methylation profiles are unique to intestinal mucosal tissue or are also present in other tissues. We have previously shown that DNA methylation profiles in saliva correlated well with DNA methylation profiles from intestinal mucosal tissue [17]. The current study compared DNA methylation profiles in saliva from individuals with and without CD, to identify DNA methylation profiles unique to GFD managed CD.…”
Section: Introductionmentioning
confidence: 85%
“…It is unknown whether the differences in DNA methylation profiles are unique to intestinal mucosal tissue or are also present in other tissues. We have previously shown that DNA methylation profiles in saliva correlated well with DNA methylation profiles from intestinal mucosal tissue [17]. The current study compared DNA methylation profiles in saliva from individuals with and without CD, to identify DNA methylation profiles unique to GFD managed CD.…”
Section: Introductionmentioning
confidence: 85%
“…By focusing on a singular tissue type, our results may be restricted to salivary tissue alone. However, salivary DNA methylation patterns have been shown to correlate with DNA methylation from blood ( Thompson et al, 2013 ; Langie et al, 2016 ), intestinal mucosa ( Hearn et al, 2019 ), and the brain ( Smith et al, 2015 ). Furthermore, saliva panels have shown proteomic changes upon hypoxic exposure in cell cultures ( Jain et al, 2020 ), suggesting the relevance of this tissue for analyzing the overall hypoxic response.…”
Section: Discussionmentioning
confidence: 99%
“…Saliva is composed of more than 99% water, and also contains white blood cells and epithelial cells, which represent the cell types of the oral mucosa. Previous DNA methylation studies comparing profiles between tissue types within individuals have shown that regions of tissue-specific differential methylation mainly map to CpG poor regions and demonstrated that methylation profiles correlating positively between saliva and diverse tissue in question ( 22 , 23 ). The viability of saliva as an alternative for less accessible tissues, including brain, lung/bronchial epithelium, and peripheral blood mononuclear cells, and in a recent study, intestinal mucosa, has been demonstrated ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous DNA methylation studies comparing profiles between tissue types within individuals have shown that regions of tissue-specific differential methylation mainly map to CpG poor regions and demonstrated that methylation profiles correlating positively between saliva and diverse tissue in question ( 22 , 23 ). The viability of saliva as an alternative for less accessible tissues, including brain, lung/bronchial epithelium, and peripheral blood mononuclear cells, and in a recent study, intestinal mucosa, has been demonstrated ( 23 ). The similar composition and function of mucosa between the oral mucosa and intestinal mucosa suggests that comparable methylation profiles between saliva and intestinal tissue might exist, and strengthens the idea that saliva has the potential to be used as an alternative for more difficult to sample tissues ( 22 ).…”
Section: Discussionmentioning
confidence: 99%